Appreciative Intelligence®: post merger communication in a public organisation. (2015) - Parkkali, Petra; Lehtimaki, Hanna; Thatchenkery, Tojo
The purpose of the study is to show how the appreciative approach can be applied to support post merger management. Appreciative Intelligence® and appreciative inquiry approaches were applied in a public organisation which had undergone an integration process where three government units merged into a single operating unit. An appreciative inquiry intervention and two follow-up interviews were conducted in the case organisation. The study contributes to the literature on the management of the post merger integration process by a focus on the human integration and by a focus on the outcomes of positive interaction.